2018
DOI: 10.1371/journal.pone.0207034
|View full text |Cite
|
Sign up to set email alerts
|

Aphid parasitism and parasitoid diversity in cotton fields in Xinjiang, China

Abstract: Aphids are major pests of cotton crops in the Xinjiang Uygur Autonomous Region in China, and parasitoids are considered as important natural enemies in regulating aphid populations. However, information on aphid parasitoids in the Xinjiang cotton fields is limited, which hinders the study of aphid-parasitoid interactions and the application of conservation biological control against cotton aphids. In this study, a 3-year survey was conducted in a large geographical range that included three primary cotton plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Aphidius gifuensis Ashmead (Hymenoptera: Braconidae) is a common endoparasitoid of many destructive aphid species (Figure 1), including Myzus persicae , Sitobion avenae and Schizaphis graminum (Pan & Liu, 2014). In China, this wasp has been widely bred and used as a biocontrol agent for more than four decades to control the green peach aphid, Myzus persicae , a severe pest on vegetables and tobaccos (Li et al, 2018; Yang et al, 2011). The life history, physiological characteristics, parasitic ability and breeding technology of A. gifuensis have been extensively studied to improve its captive breeding behaviour and aphid control efficiency (Khan et al, 2016; Li et al, 2013; Pan et al, 2018; Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Aphidius gifuensis Ashmead (Hymenoptera: Braconidae) is a common endoparasitoid of many destructive aphid species (Figure 1), including Myzus persicae , Sitobion avenae and Schizaphis graminum (Pan & Liu, 2014). In China, this wasp has been widely bred and used as a biocontrol agent for more than four decades to control the green peach aphid, Myzus persicae , a severe pest on vegetables and tobaccos (Li et al, 2018; Yang et al, 2011). The life history, physiological characteristics, parasitic ability and breeding technology of A. gifuensis have been extensively studied to improve its captive breeding behaviour and aphid control efficiency (Khan et al, 2016; Li et al, 2013; Pan et al, 2018; Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding aphid parasitoids in the cotton fields of Xinjiang, the population dynamics and parasitism rate of aphids have been investigated and the composition of the aphid parasitoid community has been determined (65% primary parasitoids, 35% hyperparasitoids). Among the four primary parasitoid species, the proportion of Binodoxys communis (Gahan) accounted for 95.19% [ 23 ]. However, up to now, there have been no reports of predation between H. variegata and aphid parasitoids.…”
Section: Introductionmentioning
confidence: 99%
“…However, the production is greatly affected by abiotic and biotic stresses. For example, in China, aphid infestation has been found to reduce G. hirsutum L. production by 30% (Li et al 2018), and salt stress has been shown to decrease cotton fiber production by 20% (Shaban et al 2018). IQD proteins are CaMBPs that play an important role in plant stress signal transduction.…”
Section: Introductionmentioning
confidence: 99%